Xanthohumol and 8-prenylnaringenin reduce type 2 diabetes–associated oxidative stress by downregulating galectin-3. Issue 1 (January 2019) - Luís, Carla; Costa, Raquel; Rodrigues, Ilda; Castela, Ângela; Coelho, Pedro; Guerreiro, Susana; Gomes, Joana; Reis, Celso; Soares, Raquel
Abstract: Background: Galectin-3 (Gal3) expression is associated with accumulation of Advanced Glycation End products (AGE), a common feature in diabetes mellitus (DM). The role of Gal3 in oxidative stress is, however, controversial, being considered in the literature to play either a protective role or exacerbating disease. Methods: Herein, we examined the interplay between Gal3 and oxidative stress in a high-fat diet -induced type 2 DMC57Bl/6 mice model. Because natural polyphenols are known to play antioxidant and anti-inflammatory roles and to modulate metabolic activity, we further evaluated the effect of xanthohumol and 8-prenylnaringenin polyphenols in this crosstalk. Results: Gal3 expression was accompanied by 3-nitrotyrosine and AGE production in liver and kidney of diabetic mice compared to healthy animals (fed with standard diet). Oral supplementation with polyphenols decreased the levels of these oxidative biomarkers as evaluated by immunohistochemistry and western blotting. Interestingly, blocking Gal3 by incubating human microvascular endothelial cells with modified citrus pectin increased 3-nitrotyrosine protein expression. Conclusions: These findings imply that Gal3 overexpression is probably controlling oxidative stress in endothelial cells. In conclusion, our results indicate that supplementation with 8-prenylnaringenin or xanthohumol reverses diabetes-associated oxidation in liver and kidney, and consequently decreases this diabetic biomarker that predispose to cardiovascular complications.